JALAN DAMAI MENUJU KEAMANAN REGIONAL: PENDEKATAN ASEAN DALAM UPAYA PENYELESAIAN KONFLIK LAUT CHINA SELATAN - R. Wildan Pratama Indra Kusumah (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
The research aimed to have an in-depth study about the development of South China Sea issue that involved countries such as China, Vietnam, Philippines, Malaysia Brunei Darussalam and the ASEAN’s role as a Regional Organization in that conflict. In general, this study wants to answer the question about “how is ASEAN’s approaches in order to reconcile South China Sea Conflict peacefully?”. To examine the problem, researcher conducted a study by using historical method that includes four research steps namely collecting of written source through literature study (heuristics), source criticism, interpretation or source analysis and historiography. Researcher also using concepts to simplify the analysis, of which are a regional organization concept, a concept of interest, an international dispute concept, a conflict concept, diplomatic concept, and the law of the sea concept. A rationalisation for this South China Sea study, because the issue remains dynamic and it is difficult to find a solution. Many perspectives regarding claims that were made by countries around the South China Sea and the potentials aspects that embedded could disrupt peace and stability in the region’s security. These issues become challenging for ASEAN. The resulting study found that: there are numbers of a mechanism such as an informal, semi-formal and formal mechanism. However, those mechanisms have not been able to resolve the conflict. Several efforts have been made to prevent military conflicts. In its development, the South China conflict has shown a more positive progress.